Glandular dose in digital mammography: Monte carlo method using voxel phantoms. (September 2016) - Tzamicha, E.; Dimitriadis, A.; Tsalafoutas, I.A.; Georgiou, E.; Tsapaki, V.; Yakoumakis, E.
Abstract : Introduction: In breast, the glandular tissues are of high sensitivity to radiation and for this reason the mean dose to the glandular tissues is the most suitable dosimetric quantity. According to the IAEA protocols the Mean Glandular Dose (MGD) is derived from measurements of the incident Air Kerma at the surface of phantom and of the HVL, using tabulated conversion coefficients. Disadvantage of the method is the fact that for calculations use a very simple model of the breast. Purpose: The purpose of this study is to assess the mean glandular dose in breast using Monte Carlo code and voxel phantoms in standing posture. Materials and methods: Fifty different phantoms (breast's thickness from 2 to 8 cm for both CC and MLO modes and for glandular fractions in the range of 1.0–100%) and EGSnrc Monte Carlo code was used to calculate the interaction of photons with matter and estimate the MGD to the breast. The calculations were made for the x-ray spectra from a Mo target (tube voltage range 26–32 kV) filtered by Rh. Results: For breast phantoms of 2.0–8.0 cm thick and 0.1–100% glandular fraction CC view acquisitions can result in a MGD of 0.452–2.572 mGy. In MLO view acquisitions MGD values ranged between 0.486 and 2.089 mGy. MGD is decreased with increasing glandularities and with increasing breast thickness in general. Conclusion: The voxel phantoms is a powerful tool for the study of breast dosimetry. When there is some knowledge of the distribution of glandular tissue within the breast, the results of this study can be used to provide for individual cases.